Artificial Intelligence In Education: Transforming Learning Through Adaptive Technologies - Kundan Kumar (Educational Administration: Theory and Practice, 2023)
This research focuses on the impact of AI in learning especially about ALTs, ITSs, and AGSs. The literature review of the articles published in the last decade and the case studies show how ALTs change the content and the manner of presenting it, how ITSs change the delivery of instructions, and how AGSs help in grading. The research investigation under consideration proves that the use of AI tools increases students’ engagement, understanding, and performance. However, the study also has some limitations for instance data privacy, data bias, and the fact that teachers are required to be trained on the use of the system. These issues should be addressed to realize the dream of AI in learning. To sum up, there are numerous possibilities for using AI in education, but threats must be controlled to get to the possibilities.